The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4141/cjss10052
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of manure nitrogen losses on total nitrogen application on agricultural land in Canada

Abstract: Yang, J. Y., Huffman, E. C., Drury, C. F., Yang, X. M. and De Jong, R. 2011. Estimating the impact of manure nitrogen losses on total nitrogen application on agricultural land in Canada. Can. J. Soil Sci. 91: 107–122. About 1 million tonnes (1 Tg=1012 g) of livestock manure N are applied to farmland in Canada each year. Comprehensive information on manure N production and losses from manure during on-farm storage, handling and field application is scarce, especially at a regional scale. However, manure N losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Unless it is indicated for a varying planting date, all projected yield changes refer to simulation results with the fixed planting date. Recommended nitrogen fertilizer rates for soil great groups (Yang et al , ) were applied in the simulations. The model was run in the sequence mode, with continuous wheat during the entire time period for the baseline or the future runs.…”
Section: Methodsmentioning
confidence: 99%
“…Unless it is indicated for a varying planting date, all projected yield changes refer to simulation results with the fixed planting date. Recommended nitrogen fertilizer rates for soil great groups (Yang et al , ) were applied in the simulations. The model was run in the sequence mode, with continuous wheat during the entire time period for the baseline or the future runs.…”
Section: Methodsmentioning
confidence: 99%
“…Generalized recommended N fertilizer rates for soil Great Groups (Huffman et al 2008;Yang et al 2011) (Table 2) were used in the simulations. For the simulations, we used N fertilizer rates recommended for wheat grown on stubble, which may result in some discrepancy between observed and simulated yields, especially in the Brown and Dark Brown soil zones, where up to 30% of wheat may have been planted into summerfallow, resulting in higher yields.…”
Section: Crop Managementmentioning
confidence: 99%
“…Therefore, the use of liquid dairy manure (LDM) as a nitrogen (N) source for the production of forage and silage crops is common. In a ranking by the proportion of farmland under the category of "very high manure N production" (≥40 kg N ha −1 ) between 1981 and 2006, Nova Scotia was found to have a proportion of farmland at 86% of not only Atlantic Canada but all Canadian provinces (Yang et al 2011). While the major cause of low NUE in Atlantic Canada is nitrate leaching (Mkhabela et al 2008;Fuller et al 2010), denitrification losses from agricultural land have also been identified as a significant N loss pathway that contributes to poor N utilization (Fan et al 1997), especially under conditions of high growing season precipitation such as those experienced in Atlantic Canada, which receives in excess of 500 mm between April and October in the major agricultural areas (Environment Canada 2014).…”
Section: Introductionmentioning
confidence: 99%